Antibacterial Mechanisms and Clinical Impact of Sitafloxacin - Elian M. A. Kuhn; Levy A. Sominsky; Marco Chittò; Edward M. Schwarz; T. Fintan Moriarty (Pharmaceuticals)
Sitafloxacin is a 4th generation fluoroquinolone antibiotic with broad activity against a wide range of Gram-negative and Gram-positive bacteria. It is approved in Japan and used to treat pneumonia and urinary tract infections (UTIs) as well as other upper and lower respiratory infections, genitourinary infections, oral infections and otitis media. Compared to other fluoroquinolones, sitafloxacin displays a low minimal inhibitory concentration (MIC) for many bacterial species but also activity against anaerobes, intracellular bacteria, and persisters. Furthermore, it has also shown strong activity against biofilms of P. aeruginosa and S. aureus in vitro, which was recently validated in vivo with murine models of S. aureus implant-associated bone infection. Although limited in scale at present, the published literature supports the further evaluation of sitafloxacin in implant-related infections and other biofilm-related infections. The aim of this review is to summarize the chemical-positioning-based mechanisms, activity, resistance profile, and future clinical potential of sitafloxacin.